A Proposed Integrated Entrepreneurship Model for Afghanistan Toward Economic Growth: Neighboring Countries' Perspective - Humta, Humayun; Ghafourzai, Hamayoun; Rashidi, Mohammad Hasham (Disclosure: Journal of Accounting and Finance, 2026)
An entrepreneur is a person who recognizes possibilities in the business world and establishes organizations to explore those prospects. Entrepreneurs contribute significantly to the expansion of the economy as well as the advancement of our society. All across the globe, there are hundreds of millions of individuals who are either actively participating in the process of attempting to establish a new start-up or who are owner-managers of a new firm. Every working hour, nearly 1700 new enterprises establish themselves in the US. For the last two decades, entrepreneurship has been viewed as a vital economic force for society due to its contributions to both the economy and social well-being in two key ways. First, new enterprises generate numerous new jobs. As new positions become available, millions may join the labour market and seek economic success. Second, new businesses may innovate and alter market structures and technology. Due to the unavailability of data from Afghanistan, neighbouring countries (Tajikistan and the Kyrgyz Republic) were selected as potential role models for economic growth. Panel data spanning from 2006 to 2020 were analyzed through an OLS regression model to draw these valid conclusions: all regressors of the model do not contribute to GNIPC except gross capital formation. Entrepreneurship, when combined with gross capital formation, could accelerate economic growth significantly, while entrepreneurship alone does not make sense for GNIPC. The moderation effect of the ease of doing business, when combined with entrepreneurship, has a significantly negative impact on economic growth, indicating that current government policies are not yet favourable enough. Future research could explore the role of psychological, sociological, and knowledge factors in the relationship between entrepreneurship and economic growth across different regions or countries.